GluN2B-containing NMDA receptors contribute to the beneficial effects of hydrogen sulfide on cognitive and synaptic plasticity deficits in APP/PS1 transgenic mice. (29th October 2016) - Yang, Yuan-Jian; Zhao, Ying; Yu, Bin; Xu, Guo-Gang; Wang, Wei; Zhan, Jin-Qiong; Tang, Zhen-Yu; Wang, Ting; Wei, Bo
Highlights: Elevating hippocampal H2 S ameliorates cognitive deficits in APP/PS1 mice. H2 S elevation restores hippocampal NMDAR-dependent LTP in APP/PS1 mice. Elevation of H2 S restores synaptic GluN2B expression and response in APP/PS1 mice. Elevation of H2 S enhances NMDAR-dependent signaling in APP/PS1 mice. Blockade of GluN2B abolishes the beneficial effects of H2 S elevation in APP/PS1 mice. Abstract: Alzheimer's disease (AD) is the most common type of clinical dementia. Previous studies have demonstrated that hydrogen sulfide (H2 S) is implicated with the pathology of AD, and exogenous H2 S attenuates spatial memory impairments in AD animal models. However, the molecular mechanism by which H2 S improves cognition in AD has not been fully explored. Here, we report that chronic administration of sodium hydrosulfide (NaHS, a H2 S donor) elevated hippocampal H2 S levels and enhanced hippocampus-dependent contextual fear memory and novel object recognition in amyloid precursor protein (APP)/presenilin-1 (PS1) transgenic mice. In parallel with these behavioral results, treating transgenic mice with NaHS reversed impaired hippocampal long-term potentiation (LTP), which is deemed as the neurobiological basis of learning and memory. At the molecular level, we found that treatment with NaHS did not affect the expression of the GluN1 and GluN2A subunits of NMDA receptor (NMDAR), but did prevent the downregulation of GluN2B subunit and restored its synaptic abundance, response and downstream signaling in the hippocampus in transgenic mice. Moreover, applying Ro 25-6981, a specific GluN2B antagonist, abolished the beneficial effects of NaHS on cognitive performance and hippocampal LTP in transgenic mice. Collectively, our results indicate that H2 S can reverse cognitive and synaptic plasticity deficits in AD model mice by restoring surface GluN2B expression and the function of GluN2B-containing NMDARs.